Sosialisasi Tentang Cyber Crime Dan Cyber Law Kepada Angkatan Muda Gereja Sion Sanggeng-Manokwari - Risma Petrus; Joice Pangulimang; Mardewi; Jennis Tonapa; Yuliana Sangka; Sabinus Rainer N.Christi (CV. Multi Kreasi Media, 2025)
An interesting issue among Indonesian society is about cybercrime and cyberlaw along with the development of technology and information that has an impact on two sides, namely positive and negative impacts on society. The negative impact of the presence of information technology that is developing so rapidly cannot be avoided. Various negative impacts that must be faced by people who lack knowledge about cybercrime and cyberlaw. The results of the implementation of socialization for the young generation of the Sion Sanggeng-Manokwari church can better understand cybercrime and cyberlaw in order to prevent and avoid cyber crime so as not to become victims or perpetrators of crimes on the digital platforms used. The implementation of this socialization uses lecture methods, simulations and questions and answers around the topics of cybercrime and cyberlaw.